Pengaruh Volume Perdagangan Saham, Order Imbalance, Frekuensi Perdagangan, Dan Volatilitas Laba Terhadap Volatilitas Harga Saham - Harimbawa, I Nyoman Triyo Rizky; Sulindawati, Ni Luh Gede Erni (Universitas Pendidikan Ganesha, 2022)
This study aims to examine the effect of Trading Volume, Order Imbalance, Trading Frequency, and Profit Volatility on Stock Price Volatility in LQ45 companies on the Indonesia Stock Exchange for the 2017-2020 period. LQ45 companies listed on the Indonesia Stock Exchange are the research sample (IDX). Purposive sampling was used in the sample selection procedure, with certain criteria adjusted so as to produce a total of 22 companies. The data used in this study were collected over a 4 year period from the official website of the Indonesia Stock Exchange and Yahoo Finance. By using the IBM SPSS version 25 application program, multiple linear regression was used for analysis in this study. The results of this study state that stock trading volume, order imbalance, and earnings volatility partially have a positive and significant effect on stock price volatility, at the same time trading frequency has no effect on stock price volatility. To get the highest profit, investors who want to put their money in a company in the capital market must carefully examine the company both technically and fundamentally.